Pelatihan Pemanfaatan Platform Quora Sebagai Sumber Pembelajaran Reading pada Siswa SMA IT Imam Syafii 2 Pekanbaru - Estika Satriani; Andi Idayani; Resy Oktadela; Destry Priyanti Kadir (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service activity aims to improve students’ English reading ability and digital literacy by using Quora as an authentic digital learning platform. A total of 25 students and 2 English teachers from SMAIT Imam Syafii 2, Pekanbaru, participated as partners in this program. The activity was implemented using a participatory training approach based on digital practice. Evaluation instruments consisted of questionnaires, which were analyzed descriptively using interval assessment techniques. The results of the program showed that the use of Quora as a digital reading medium, which provides authentic reading sources, diverse topics, and opportunities for real interaction with global users, was effective in improving students’ reading comprehension and digital literacy. In addition, students demonstrated increased motivation and self-confidence in understanding and responding to English texts. This community service activity highlights the importance of continuous mentoring in integrating technology into English reading instruction and is expected to serve as a replicable model of digital platform-based reading instruction for other secondary school contexts.